Superman and Philosophy What Would the Man of Steel Do - Irwin, William 1970- (The Blackwell Philosophy and Pop Culture Ser., 2013)
Go beyond the cape and into the mind of the Man of Steel, in time for release of Zack Snyder's Man of Steel movie and Superman's 75th anniversary He has thrilled millions for 75 years, with a legacy that transcends national, cultural, and generational borders, but is there more to the Man of Steel than just your average mythic superhero in a cape? The 20 chapters in this book present a fascinating exploration of some of the deeper philosophical questions raised by Superman, the Last Son of Krypton and the newest hero in the Blackwell Philosophy and Pop Culture arsenal